Reduksi kolesterol pada sotong (sepia sp.) dengan cara pengolahan yang berbeda - Ulfa Fairus; Suparmi '; Edison ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was intended to reduce cholesterol content of cuttlefish (Sepiasp.) processed by boiling and steaming. Three kilograms of fresh cuttlefish weretaken from a fish market in Pekanbaru. The cuttlefish was washed and groupedinto 3 groups of one kilogram each. First group was boiled at 100oC, second groupwas steamed at 101oC and third group was fresh cuttlefish (control). Cuttlefishbefore and after boiling or steaming was weighed and analysed for cholesterolcomposition, moisture, fat and protein. The result indicated that the cholesterolcomposition of boiled cuttlefish, steamed cuttlefish, and control was 2,76 mg/g,2,07 mg/g, and 5,74 mg/g respectively. Moisture, fat and protein of cuttlefishboiled cuttlefish was 74,98%, 0,22%, 16,17% respectively; steamed cuttlefishwas 67,66%, 0,15%, and 19,75% respectively; and control was 84,24%, 0,35%,24,90% respectively. The result showed that percentage of meat, head, visceraeand internal shell of boiled cuttlefish was 39,04%, 10,70%, 4,69%, 5,55%respectively; steamed cuttlefish was 37,77%, 12,51%, 3,57% respectively; andcontrol was 60,54%, 22,51%, 11,33% respectively.Keywords : Cuttlefish (Sepia sp), reduction , cholesterol